Penetration and mixing of filler wire in hybrid laser welding - Suder, Wojciech; Ganguly, Supriyo; Williams, Stewart W.; Yudodibroto, Bagus Y. B. (Elsevier, 2021)
Modern lasers allow achievement of full penetration single pass welds in steel plates with thicknesses exceeding 20 mm, at welding speeds much greater than any traditional arc-based process. However, the addition of filler wire, which in most structural welds is required to ensure good mechanical properties, is more challenging. Most welds from laser and hybrid welding with filler feeding start to exhibit inhomogeneous fusion zones above a particular joint thickness. The filler consumable segregates near the top section of the joint, while the bottom forms by the re-melted parent metal, which negatively affects mechanical properties. In this work, the homogeneity of laser-arc hybrid welds was investigated experimentally, using a filler wire with a signature element, whose distribution was measured. Three different bevels with different geometry were used to study the flow of liquid filler wire across the joint. The laser and arc parameters were varied to establish the dominant forces responsible for the transport of filler wire and weld homogeneity. The results indicate that hybrid welds are susceptible to form inhomogeneous fusion zones and to achieve acceptable welds, two aspects need to be controlled. The first one is the average content of an alloying element in the meltpool, which is mainly controlled by the wire composition, its deposition rate and dilution with the parent metal. Whilst the second aspect being the weld homogeneity. It has been found that the laser power density is predominantly responsible for the transport of the consumable metal across the material. Furthermore, most processing parameters, such as the arc power or laser power, play contradicting roles, improving one aspect and simultaneously hindering another. The best way of achieving fully homogenous welds with known composition is by applying sufficient wire deposition, to satisfy the compositional requirement, and then provide enough laser power density to transport it across the full thickness.
Keywords: Hybrid laser welding; Wire mixing; Weld homogeneity; Productivity limit